Topographic and Neurovascular Determinants of Dental Implant Complications: An Anatomical Review for Surgical Planning - K. Mardaleishvili; T. Baramidze (International Journal of Medical Science and Clinical Research Studies, 2026)
Dental implantology is performed within an anatomically compact region in which osseous, vascular, lymphatic, sinus, and neural structures lie in close proximity. The objective of this narrative review is to reorganize the anatomical content of the source manuscript into a journal-style article focused on topographic and neurovascular risk assessment. The review examines maxillary and mandibular anatomical zones that determine surgical safety, including the maxillary sinus, Schneiderian membrane, nasopalatine canal, thin buccal cortical plate, infraorbital region, inferior alveolar canal, mental foramen, lingual cortical plate, and floor-of-mouth vascular spaces. Particular attention is given to how anatomical variation contributes to sinus perforation, implant malposition, intraosseous bleeding, hematoma, thermal osteonecrosis, and trigeminal-branch injury. The article emphasizes CBCT-based planning, preservation of safety margins, atraumatic osteotomy, copious irrigation, and systematic postoperative neurosensory monitoring. A precise anatomical framework remains essential for reducing preventable complications and improving functional outcomes after dental implant placement.